Pembangunan Sistem Aplikasi Heloners Sebagai Platform Penyewaan Jasa Perawat - Renaldin Suinto Zai; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Nurses are one of the health workers who have the responsibility to provide professional health services to the community. On the other hand, many nurses are still paid with a small nominal range. In addition, the high number of nurse graduates is not proportional to the number of job openings for nurses. If viewed from the perspective of the community as a recipient of nursing services, there are people who need nurses' services to come to the desired home or location. Conventional home nurse bookings have several drawbacks, such as the uncertain price of ordering nurse services and the absence of a patient's medical record as a tool for nurses to apply nursing care. In this study a software application system was built that had a leasing business process between the business owner to the client and between the nurse and client. This application system is named Heloners. In this study an object-oriented web application development approach is used. The results of this study were 33 functional requirements and 1 non-functional requirement. The results of the tests carried out yielded 100% valid for all test cases.